Biological Activities Underlying the Therapeutic Effect of Quercetin on Inflammatory Bowel Disease - Yong-Li Lyu; Hai-Feng Zhou; Jia Yang; Fa-Xi Wang; Fei Sun; Jun-Yi Li (Hindawi Limited, 2022)
Inflammatory bowel disease (IBD) is a chronic autoimmune disorder stemming from unrestrained immune activation and subsequent destruction of colon tissue. Genetic susceptibility, microbiota remodeling, and environmental cues are involved in IBD pathogenesis. Up to now, there are limited treatment options for IBD, so better therapies for IBD are eagerly needed. The therapeutic effects of naturally occurring compounds have been extensively investigated, among which quercetin becomes an attractive candidate owing to its unique biochemical properties. To facilitate the clinical translation of quercetin, we aimed to get a comprehensive understanding of the cellular and molecular mechanisms underlying the anti-IBD role of quercetin. We summarized that quercetin exerts the anti-IBD effect through consolidating the intestinal mucosal barrier, enhancing the diversity of colonic microbiota, restoring local immune homeostasis, and restraining the oxidative stress response. We also delineated the effect of quercetin on gut microbiome and discussed the potential side effects of quercetin administration. Besides, quercetin could serve as a prodrug, and the bioavailability of quercetin is improved through chemical modifications or the utilization of effective drug delivery systems. Altogether, these lines of evidence hint the feasibility of quercetin as a candidate compound for IBD treatment.